Gun Digest shooter's guide to AKS - Vorobiev, Marco (Gun Digest Books, an imprint of F+W Media, Inc, 2016)
A practical guide for every AK shooter, serving as a valuable reference manual for the expert, average or novice shooter who wants to learn the fundamentals of operation, maintenance and accessories for the AK rifle.